2015
DOI: 10.4103/0973-8398.154710
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of gastro-retentive floating microballoons of acrycoat S-100 bearing carvedilol

Abstract: G astro-retentive dosage forms have potential for use as controlled/sustained release drug delivery systems. Multiple-unit systems avoid the "all-or-none" gastric emptying nature of single-unit system. The present study was to formulate and develop a gastroretentive release delivery system for carvedilol as model drug using Acrycoat S 100 as a polymer. Carvedilol is widely used for the therapeutic management of hypertension, congestive heart failure, but it has several drawbacks such as short biological half-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 11 publications
4
12
5
1
Order By: Relevance
“…In the isolated state the IR and Raman intensities of both d(N1eH) and d(N3eH) bands appear similar, but in the tetramer form that of d(N3eH) is slightly higher than that of d(N1eH), in accordance to that found experimentally in the IR and Raman spectra. Thus, the experimental IR band observed with weak intensity at 1456 cm À1 in KBr pellet was related to d(N3eH) mode, in agreement to its scaled frequency in the tetramer form at 1452 cm À1 , whereas we have not detected and assigned a band to d(N3eH) mode, in accordance to its null IR intensity predicted, although other authors have observed bands at 1310 [25] and 1334 [27] cm À1 , that we have reassigned to this mode. The Raman intensity of the d(N3eH) mode is larger than that of the d(N1eH) mode, in agreement with the Raman band with weak intensity detected at 1414 cm À1 and assigned as d(N3eH), and to the very weak band at 1280 cm À1 related to d(N1eH).…”
Section: Computed Wavenumbers Of 6-aminousupporting
confidence: 89%
See 4 more Smart Citations
“…In the isolated state the IR and Raman intensities of both d(N1eH) and d(N3eH) bands appear similar, but in the tetramer form that of d(N3eH) is slightly higher than that of d(N1eH), in accordance to that found experimentally in the IR and Raman spectra. Thus, the experimental IR band observed with weak intensity at 1456 cm À1 in KBr pellet was related to d(N3eH) mode, in agreement to its scaled frequency in the tetramer form at 1452 cm À1 , whereas we have not detected and assigned a band to d(N3eH) mode, in accordance to its null IR intensity predicted, although other authors have observed bands at 1310 [25] and 1334 [27] cm À1 , that we have reassigned to this mode. The Raman intensity of the d(N3eH) mode is larger than that of the d(N1eH) mode, in agreement with the Raman band with weak intensity detected at 1414 cm À1 and assigned as d(N3eH), and to the very weak band at 1280 cm À1 related to d(N1eH).…”
Section: Computed Wavenumbers Of 6-aminousupporting
confidence: 89%
“…This assignment finds further support from that reported experimentally in 5-aminoU at 418 cm À1 (IR) and 418.9 cm À1 (Raman) [62], in 5-chlorouracil at 446 cm À1 (IR) and 457 cm À1 (R) [66], in 6-chlorouracil at 451 cm À1 (IR) and 443 cm À1 (R) [12], and in 5-fluorouracil at 419 cm À1 (IR) and 413 cm À1 (R) [65]. The experimental bands reported at 430 [25], 416 [26] and 450, 430 [27] cm À1 were reassigned to this inplane bending mode, instead of its assignment by these authors and 734 (Raman) cm À1 , and it was related to the experimental band at 764 cm À1 in IR and 768 cm À1 in Raman. This assignment finds also support with that reported experimentally in uracil molecule at 769 cm À1 [51], in 5-chlorouracil at 743 (IR) and 740 cm À1 (Raman) [66], in 6-chlorouracil at 758 (IR) and 723.3 cm À1 (Raman) [58], and in 5-fluorouracil at 740 cm À1 (IR) [67].…”
Section: Computed Wavenumbers Of 6-aminoumentioning
confidence: 95%
See 3 more Smart Citations